Preferensi Konsumen dan Pengembangan Strategis Pasar Ayam Beku di Sumatera Barat: Pendekatan SWOT - QSPM - Budiharto, Agus; Hellyward, James; Madarista, Fuad; Putri, Budi Rahayu Tanama (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2026)
The transformation of modern food systems has increased public awareness of food safety, quality, and hygiene, including the consumption of animal protein such as chicken. However, the frozen chicken market share in West Sumatra remains relatively low due to strong preferences for fresh chicken, quality perceptions, cultural factors, and limited cold chain infrastructure. This study aims to analyze consumer preferences, identify internal and external factors, and formulate development strategies for the frozen chicken market. This research applies a qualitative approach through observation and in-depth interviews with academics, distributors, Horeca actors, frozen food retailers, and consumers in Padang and Bukittinggi. The data were analyzed using SWOT, IFE, EFE, IE Matrix, and QSPM. The results show an IFE score of 2.83 and an EFE score of 2.77, placing the sector in quadrant V. The main strategy is market penetration and consumer education.